2(w-3)-6=-4w+3(w-5)

Simple and best practice solution for 2(w-3)-6=-4w+3(w-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(w-3)-6=-4w+3(w-5) equation:


Simplifying
2(w + -3) + -6 = -4w + 3(w + -5)

Reorder the terms:
2(-3 + w) + -6 = -4w + 3(w + -5)
(-3 * 2 + w * 2) + -6 = -4w + 3(w + -5)
(-6 + 2w) + -6 = -4w + 3(w + -5)

Reorder the terms:
-6 + -6 + 2w = -4w + 3(w + -5)

Combine like terms: -6 + -6 = -12
-12 + 2w = -4w + 3(w + -5)

Reorder the terms:
-12 + 2w = -4w + 3(-5 + w)
-12 + 2w = -4w + (-5 * 3 + w * 3)
-12 + 2w = -4w + (-15 + 3w)

Reorder the terms:
-12 + 2w = -15 + -4w + 3w

Combine like terms: -4w + 3w = -1w
-12 + 2w = -15 + -1w

Solving
-12 + 2w = -15 + -1w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add 'w' to each side of the equation.
-12 + 2w + w = -15 + -1w + w

Combine like terms: 2w + w = 3w
-12 + 3w = -15 + -1w + w

Combine like terms: -1w + w = 0
-12 + 3w = -15 + 0
-12 + 3w = -15

Add '12' to each side of the equation.
-12 + 12 + 3w = -15 + 12

Combine like terms: -12 + 12 = 0
0 + 3w = -15 + 12
3w = -15 + 12

Combine like terms: -15 + 12 = -3
3w = -3

Divide each side by '3'.
w = -1

Simplifying
w = -1

See similar equations:

| 0=0.5*(x-0.5+0.5x-0.33) | | 9(x+4)=-27 | | 12-0.75(x+15)=4 | | f/3=2 | | x/2-10=0 | | 16=2s+-40 | | y=45x+160 | | 7+6g=25 | | X=.75x+6 | | 51=-9d-8d | | 2*22/7*50 | | 405=15b | | -2y+40=8y | | 2x22/7x50 | | -9+5x=7x-5 | | 14-6p=-16 | | 6(12+x)=360 | | n/3-6=1 | | 2(5x-3)=44 | | 3(n-7)-(4-2n)=4n | | 5y+-17=58 | | 6a+4c=238 | | X-0.5*((1-X)-0.33)=0 | | -16t^2+48t+16=0 | | 0.0588= | | 2/10=30/x | | -3(x-14)+9x=6x+42 | | 3j=-12 | | 2(y)=70-4x | | -3=x+9-4x | | 1=pqr/1 | | 7-3d=10 |

Equations solver categories